2013
DOI: 10.1007/s00277-013-1676-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased promyelocytic-derived microparticles: a novel potential factor for coagulopathy in acute promyelocytic leukemia

Abstract: The frequent serious bleeding and thrombotic complications in acute promyelocytic leukemia (APL) are major causes of early mortality, but the complex mechanisms causing the bleeding have not been completely elucidated. Because microparticles (MPs) are known to be elevated in thromboembolic disorders, we hypothesized a role for MPs in the pathogenesis of coagulopathy in APL. MPs were isolated from 30 APL patients and 20 healthy subjects and from cultured NB4/APL cells. The morphology of the MPs was examined, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 29 publications
1
19
0
2
Order By: Relevance
“…A previous study found increased levels of MPs in patients with pancreatic and metastatic breast cancer compared to controls (22). The MPs that are found in patients with acute promyelocytic leukaemia are mainly TF + MPs that are derived from promyelocytic cells, with low levels of PMPs, which may be the result of decreased platelet counts, as reported by Ma et al (23). In addition, patients with venous thromboembolism (VTE) exhibit an increased level of MPs compared with patients without VTE (24).…”
Section: Discussionmentioning
confidence: 71%
“…A previous study found increased levels of MPs in patients with pancreatic and metastatic breast cancer compared to controls (22). The MPs that are found in patients with acute promyelocytic leukaemia are mainly TF + MPs that are derived from promyelocytic cells, with low levels of PMPs, which may be the result of decreased platelet counts, as reported by Ma et al (23). In addition, patients with venous thromboembolism (VTE) exhibit an increased level of MPs compared with patients without VTE (24).…”
Section: Discussionmentioning
confidence: 71%
“…Moreover an increased frequency of mechanical complications coupled with longer dwell times of PICCs compared with CVDs might also increase the risk of DVT. 33 Recently, the role of TF circulating in blood in association with subcellular membrane vesicles, so-called plasma MPs in the 22,34 Microparticles are cell-derived membrane fragments measuring 0.1 to 1.0 mm, originating from platelets, blood cells, endothelial cells, or malignant cells. Soluble or free TF found in the plasma is carried by MPs and binds directly to factor VIIa.…”
Section: Infectious Complicationsmentioning
confidence: 99%
“…The procoagulant state in APL is partially due to the TF-dependent procoagulant properties of circulating promyelocytic-derived microparticles (MPs). 22 Leukocytosis is commonly observed in leukemia. Studies on the pathophysiology of leukostasis and tissue infiltration by leukemic blast cells have revealed that cytokines (tumor necrosis factor-alpha [TNF-alpha] and interleukin 1b [IL1b]) secreted by leukemic cells, together with direct contact between adhesion receptors expressed by blasts and endothelial cells, are responsible for endothelial activation, that leads to the activation of the clotting cascade and thrombotic complications.…”
Section: Prothrombotic Factors Produced By Leukemic Cellsmentioning
confidence: 99%
“…plasma levels of D-dimer in APL patients [50]. APL cellderived MPs decreased coagulation time and increased thrombin generation in a TF-dependent manner [50]. Exposure of leukemia cells to anthracycline increased the release of TF ?…”
Section: Hypercoagulabilitymentioning
confidence: 99%
“…MPs might also be involved in hypercoagulability in APL patients. plasma levels of D-dimer in APL patients [50]. APL cellderived MPs decreased coagulation time and increased thrombin generation in a TF-dependent manner [50].…”
Section: Hypercoagulabilitymentioning
confidence: 99%